The optimal calibration hypothesis: how life history modulates the brain's social pain network - Chester, David S.; Pond, Richard S.; Richman, Stephanie B.; DeWall, C. Nathan (Frontiers in Evolutionary Neuroscience, 2012)
A growing body of work demonstrates that the brain responds similarly to physical and social injury. Both experiences are associated with activity in the dorsal anterior cingulate cortex (dACC) and anterior insula. This dual functionality of the dACC and anterior insula underscores the evolutionary importance of maintaining interpersonal bonds. Despite the weight that evolution has placed on social injury, the pain response to social rejection varies substantially across individuals. For example, work from our lab demonstrated that the brain’s social pain response is moderated by attachment style: anxious-attachment was associated with greater intensity and avoidant-attachment was associated with less intensity in dACC and insula activation. In an attempt to explain these divergent responses in the social pain network, we propose the optimal calibration hypothesis, which posits variation in social rejection in early life history stages shifts the threshold of an individual’s social pain network such that the resulting pain sensitivity will be increased by volatile social rejection and reduced by chronic social rejection. Furthermore, the social pain response may be exacerbated when individuals are rejected by others of particular importance to a given life history stage (e.g., potential mates during young adulthood, parents during infancy and childhood).